SOCIO-PSYCHOLOGICAL STATES OF ADOLESCENTS IN MODERN SOCIETY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article explores the socio-psychological states of adolescents in modern society as well as the age characteristics of adolescent periods of crisis. It also talks about individual psychological characteristics found in adolescents.